Good faith collaboration the culture of Wikipedia - Reagle, Joseph Michael (History and foundations of information science., 2010)
Wikipedia, the online encyclopedia, is built by a community - a community of Wikipedians who are expected to "assume good faith" when interacting with one another. In Good Faith Collaboration, Joseph Reagle examines this unique collaborative culture.